1996
DOI: 10.1016/0014-5793(96)00682-5
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of reconstituted influenza virus envelopes with liposomes mediated by streptavidin/biotin interactions

Abstract: Reconstituted influenza virus envelopes (virosomes)containing the viral hemagglutinin (HA) represent an efficient fusogenic cellular delivery system. By interaction of HA with its natural receptors, sialylated lipids (gangliosides) or proteins, virosomes bind to cells and, following endocytic uptake, deliver their contents to the cytosol through fusion from within acidic endosomes. Here, we show that binding to sialic acid is not necessary for fusion. In the presence of streptavidin, virosomes containing a bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…However, as both DTT-based inhibition of fusion and the formation of gp64 HC were observed in infected Sf9 cells (expressing all viral envelope proteins including the hypothetical “binding” protein), we believe that main conclusions of our study pertain to biologically relevant gp64-mediated fusion. Similar to baculovirus, influenza HA fusion also appears to be independent of the specific binding mechanism ( Schoen et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as both DTT-based inhibition of fusion and the formation of gp64 HC were observed in infected Sf9 cells (expressing all viral envelope proteins including the hypothetical “binding” protein), we believe that main conclusions of our study pertain to biologically relevant gp64-mediated fusion. Similar to baculovirus, influenza HA fusion also appears to be independent of the specific binding mechanism ( Schoen et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that specific interaction of HA1 with sialic acid is not a prerequisite for fusion. HA-expressing membranes (HA membranes) readily fuse with bound membranes lacking receptors (Schoen et al, 1996;White et al, 1982), although the kinetics of fusion can differ from that in the presence of receptors (Alford et al, 1994;de Lima et al, 1995;Niles and Cohen, 1993;Stegmann et al, 1995). Furthermore, the HA1-sialic acid connection is not required for fusion completion at low pH-independent stages of fusion subsequent to low pH triggering (Chernomordik et al, 1997Schoch et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that influenza virus HA‐mediated fusion is independent of binding to sialic acid [15]. The binding step can be replaced by any other molecular interaction such as biotin/streptavidin interactions, which indicates that fusion is independent of any specific behavioral property of the underlying (cell surface) protein or lipid to which the sialic acid is linked.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane fusion experiments were carried out essentially as described before [15]. In short, virosomes at a final concentration of 2.5 μM phospholipid and donor membranes (either erythrocyte ghosts or OVCAR‐3 membrane vesicles at a final concentration of 50 μM or 200μM phospholipid, respectively) were added to a thermostatted and stirred cuvette that contained HBS.…”
Section: Methodsmentioning
confidence: 99%